GERMAN DEVELOPMENT POLICY: MAIN OBJECTIVES, PRINCIPLES AND STRUCTURE - Ekaterina P. Timoshenkova (Institute of Europe Russian Academy of Sciences, 2021)
The Federal Republic of Germany plays not only a leading role in the EU, but is also a global player with interests around the world. At the same time, the FRG has succeeded in establishing itself as an «honest broker» and mediator in international conflicts. Its image as a democratic state under the rule of law with a developed social system and a stable economic development model is attractive to many countries, including «developing» ones, which aspire to cooperate with Germany and are guided by its experience and recommendations. The German Development Policy is an important instrument of soft power, which is used not only for humanitarian purposes, but also to meet specific economic and political objectives. Thanks to its effective development policy, Germany manages to maintain contacts with representatives of various political elites, even if relations with the official government deteriorate. Non-governmental organizations play a major role in promoting German interests. Moreover, an outside observer might get the impression that it is these organizations that largely determine the development policy of the Federal Republic of Germany. In order to understand how this foreign policy mechanism functions, what its strengths are, and what role the state and civil society actors (NGOs, party-political foundations, charities, etc.) play in development policy, it is necessary to analyze the structure, goals and principles of German development policy. This article is devoted to this question.